Análise da motivação dos funcionários perante intervenções ergonômicas no ambiente de trabalho - Fröhlich, Angélica Ferraz Antunes (Universidade do Vale do Rio dos Sinos, 2021)
Currently, companies are increasingly concerned with the well-being of their employees, seeking innovations that provide better working conditions. Increasing the quality of life and taking care of people’s health are the main objectives to be achieved with these changes and it is clear that with this it is expected that people are motivated and more engaged in the search for the best results and feel safe to carry out their activities. This paper will show how an improvement focused on ergonomics can influence the motivation of employees of an automotive industry, through the application of a qualitative and quantitative satisfaction questionnaire.
Keywords: Colaboração; Entusiasmo; Ergonomia; Motivação; Collaboration; Enthusiasm; Ergonomics; Motivation